Ethylene responsive transcription factor ERF109 retards PCD and improves salt tolerance in plant. Issue 1 (December 2016) - Bahieldin, Ahmed; Atef, Ahmed; Edris, Sherif; Gadalla, Nour; Ali, Hani; Hassan, Sabah; Al-Kordy, Magdy; Ramadan, Ahmed; Makki, Rania; Al-Hajar, Abdulrahman; El-Domyati, Fotouh
Abstract Background The ultimate goal of this work was to detect the role of transcription factors (TFs) concordantly expressed with genes related to programmed cell death (PCD) during PCD and salt stress. This work was based on the hypothesis that TFs and their driven genes likely co-express under different stimuli. The conserved superfamily ethylene responsive factor (AP2/ERF) draw attention of the present study as it participates in the response to biotic and abiotic stimuli as well as to program cell death (PCD). Results RNA-Seq analysis was done for tobacco (N. benthamiana ) leaves exposed to oxalic acid (OA) at 20 mM for 0, 2, 6, 12 and 24 h to induce PCD. Genes up-regulated after 2 h of OA treatment with known function during PCD were utilized as landmarks to select TFs with concordant expression. Knockdown mutants of these TFs were generated in tobacco via virus induced gene silencing (VIGS) in order to detect their roles during PCD. Based on the results of PCD assay, knockout (KO) T-DNA insertion mutants of Arabidopsis as well as over-expression lines of two selected TFs, namely ERF109 and TFIID5, analogs to those in tobacco, were tested under salt stress (0, 100, 150 and 200 mM NaCl). Conclusions Results of knockdown mutant tobacco cells confirmed the influence of these two TFs during PCD. Knockout insertion mutants and over-expression lines indicated the role of ERF109 in conferring salt tolerance in Arabidopsis.